Brazeability and microstructure of ag-28cu microjoining filler produced by high energy ball milling - SHARMA, ASHUTOSH; CHAE, MYOUNG JIN; AHN, BYUNGMIN (Archives of Metallurgy and Materials, 2020)
In this paper, we have studied the evolution of morphology and brazing behavior of Ag-28Cu alloy filler processed by high energy ball milling. The milling of the powder mixture was carried out for 40 h. The structural and morphological analyses were performed by the X-ray diffraction and scanning electron microscopy. The melting temperature of the braze filler was determined by differential thermal analysis. The filler wetting properties were assessed from the spread area ratio measurements on various Ti substrates. The results indicate that the ball milling can effectively depress the filler melting point and enhance the brazeability. The milled powder mixture showed Ag(Cu) solid solution with a crystallite size of 174-68 nm after 40 h. It was shown that the high energy ball milling can be a potential method to develop low temperature brazing fillers for advanced microjoining applications.
Keywords: Brazing fillers; Evolution of morphologies; High-energy ball milling; Low temperatures; Morphological analysis; Potential methods; Powder mixtures; Wetting property; Ball milling; Dissimilar; Filler; Microjoining; Microstructure